Charge Reservoirs in an Expanded Halide Perovskite Analog: Enhancing High‐Pressure Conductivity through Redox‐Active Molecules. (3rd May 2022) - Matheu, Roc; Ke, Feng; Breidenbach, Aaron; Wolf, Nathan R.; Lee, Young; Liu, Zhenxian; Leppert, Linn; Lin, Yu; Karunadasa, Hemamala I.
Abstract: As halide perovskites and their derivatives are being developed for numerous optoelectronic applications, controlling their electronic doping remains a fundamental challenge. Herein, we describe a novel strategy of using redox‐active organic molecules as stoichiometric electron acceptors. The cavities in the new expanded perovskite analogs (dmpz)[Sn2 X6 ], (X=Br − (1Br ) and I − (1I )) are occupied by dmpz 2+ ( N, N ′‐dimethylpyrazinium), with the LUMOs lying ca. 1 eV above the valence band maximum (VBM). Compressing the metal‐halide framework drives up the VBM in 1I relative to the dmpz LUMO. The electronic conductivity increases by a factor of 10 5 with pressure, reaching 50(17) S cm −1 at 60 GPa, exceeding the high‐pressure conductivities of most halide perovskites. This conductivity enhancement is attributed to an increased hole density created by dmpz 2+ reduction. This work elevates the role of organic cations in 3D metal‐halides, from templating the structure to serving as charge reservoirs for tuning the carrier concentration. Abstract : Redox‐active organic cations can act as charge reservoirs in the expanded perovskite analog (dmpz)[Sn2 I6 ]. Material compression increases electronic conductivity by five orders of magnitude. This conductivity rise is attributed to an increased hole density in the valence band, caused by electron transfer to the redox‐active molecules.